Toward the Great Divergence: economic growth in the Yangzi Delta, 1393-1953 - Zhai, R (2022)
This dissertation examines the economic growth process of the Yangzi Delta, one of China’s most developed sub-regions, from 1393 to 1953. For the first time in the literature, an annual frequency GDP series based on an output-based approach is constructed. The dissertation is split into two sections: measuring economic growth and analysing economic growth. As part of measuring economic growth, I discuss local population and land, agriculture, and industry and services in Chapters Two, Three, and Four, respectively. Chapter Five in the section on analysing economic growth briefly reviews the process of local economic growth over several centuries using constructed GDP data. The Great Divergence Debate is then discussed in Chapter Six, which places the Yangzi Delta’s economic growth in an international comparative framework.